Suitability assessment for oil palm (Elaeis guineensis) and coconut (Cocus nucifera) cultivation in coastal plain sands of South Southern Nigeria - Faith Ehinomhen Okunsebor; Aigboghosa Samson Umweni; Lucky Agbogun (Jurnal Ilmu Pertanian, 2021)
Some soils of coastal plain sands in South Southern Nigeria were assessed for oil palm and coconut cultivation. This research was carried out to evaluate the soils of the study area using rigid grid soil survey methodology at detailed scale. The study area (128.11 ha) was delineated into four soil mapping units based on soil type. A pedon was sunk in each mapping unit and described according to FAO. Three soil orders, including Entisols (Ahiara), Inceptisols (Kulfo) and Ultisols (Orlu), were identified. Parametric and limitation methods of land suitability evaluation were used. Major limitations to assessment were climate (mean annual temperatures) and soil physical properties (texture/structure). Aggregate suitability rating (both actual and potential) showed that Ultisols (pedons 3 and 4, covering 56.73 ha) was moderately suitable (S2) for coconut and marginally suitable (S3) for oil palm, Inceptisols (pedon 2, covering 54.25 ha) was marginally suitable (S3) for coconut but not suitable (NS) for oil palm, and Entisols (Pedon 1covering 17.13 ha) was not suitable (NS) for any of the crops. Thus, area with Entisols should not be used for cultivation of any of the crops due to major limitation in texture. Moreover, both assessment approaches captured the major limitations. Therefore, the use of any of the approaches employed in this study and for these crops becomes a matter of choice as both of them showed no major differences in the application of their procedures.